Data migration project of Takaful integrated system - Munirah Akmal Murat, author; Othman Mohd. Yusop, supervisor; Yusree Yahaya, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (Kuala Lumpur : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Sains (Real Time Software Engineering)) - Universiti Teknologi Malaysia, 2004